11=-5x-5x-9

Simple and best practice solution for 11=-5x-5x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=-5x-5x-9 equation:


Simplifying
11 = -5x + -5x + -9

Reorder the terms:
11 = -9 + -5x + -5x

Combine like terms: -5x + -5x = -10x
11 = -9 + -10x

Solving
11 = -9 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
11 + 10x = -9 + -10x + 10x

Combine like terms: -10x + 10x = 0
11 + 10x = -9 + 0
11 + 10x = -9

Add '-11' to each side of the equation.
11 + -11 + 10x = -9 + -11

Combine like terms: 11 + -11 = 0
0 + 10x = -9 + -11
10x = -9 + -11

Combine like terms: -9 + -11 = -20
10x = -20

Divide each side by '10'.
x = -2

Simplifying
x = -2

See similar equations:

| =13-v | | g/2-4g=20 | | (-2/5)x=-4/15 | | h-3/3=4 | | 5(6+5a)=4a-12 | | 7n+12*13n-16*6n=360 | | (7n+12)(13n-16)(6n)=360 | | 3h-10h=-14 | | 2c-2b=-14 | | Ln(x+7)+ln(x)=ln(18) | | -84=-4(3-4n)+2n | | 2(c-14)=37 | | 41=3x+25 | | z-9/-2=-3 | | t-22=14 | | 3r-6=6-r | | 3000/450 | | -.15x=60 | | -26=x/4=9 | | K^2-10k-30=0 | | g+4g-3=12 | | -2v+1+2v=-7+v | | -26=x/4 | | -(x-4)=2x-7 | | -16+19q=20q | | (-2/3)x=-4/3 | | 2c+-3c=2 | | -(x+3)=9 | | 2x=19/5=3 | | 4m-3-4n=11 | | -15c+-10c+-10=-10 | | 8+6p=8+6p |

Equations solver categories